Profil Literasi Lingkungan dan Keterampilan Berpikir Kreatif Siswa SMA pada Materi Green Chemistry dan Pembangunan Berkelanjutan di Kota Tidore Kepulauan - Tamrin Taher; Susilawati Husaen; Lu'luul Fathimatuzzuhro Algus; Nurhayat Ahmad; Jawia Ali; Sistri Soleman (CAHAYA: Journal of Research on Science Education, 2026)
This study addresses the fundamental question of what the real situation of senior high school students’ environmental literacy and creative thinking skills looks like, and why this needs to be surveyed, in the context of green chemistry and sustainable development content within the Science curriculum. The researchers’ position is that of describing in depth the current profile of both competencies and their underlying dimensions, prior to drawing implications for future learning. A survey method was employed involving 169 tenth-grade students from three state senior high schools in Tidore Kepulauan City. Data were collected using validated environmental literacy and creative thinking tests, each consisting of four dimensions referring to the NAAEE  framework and Torrance's theory. The findings consistently show that both variables fall into the low category across all three schools, with overall mean scores of 52.4 for environmental literacy and 48.9 for creative thinking, both well below the minimum threshold of 60. The lowest-performing dimensions were responsible behavior (45.4) for environmental literacy and originality (41.7) for creative thinking, both reflecting a similar pattern: students possess adequate foundational knowledge and idea-generation ability but struggle to translate these into responsible action and original ideas. These findings provide an in-depth picture of students’ real competency situation and a strong empirical basis for prioritizing these two dimensions in future learning interventions.